Miguel Grau and International Humanitarian Law - Laguerre Kleimann, Michel (2021)
The attitude of Captain Miguel Grau Seminario, during the naval campaign that he led in the international conflict of 1879 has characteristics that are framed withinof International Humanitarian Law, a branch of International Law that had as bases -among others- the Geneva Convention of 1864. In this sense, and from the Hague Convention of 1899 that dealt with the adaptation to maritime warfare of the principles of the Geneva Convention, Peru only acceded to it in the year of 1903. In this way, the present work will seek to argue from the law and history the aspects that would make the Knight of the Seas a Precursor of Law Humanitarian International of the war at sea, since it acted without a framework established legal system - neither national nor international - related to the humanitarian aspecto of the war at sea, and without receiving written instructions - neither general nor specific - on the subject, beyond the custom that was considered law current. From the two cases presented, it can be deduced that he would have acted having as base reason for it and / or customary law. In fact, the humanitarian actions of Grau that will be presented in this work, not were the first carried out in world maritime history, but yes, it could be considered a pioneer on this side of the South American Pacific. However, more Regardless of the possibility that it was the initial, nothing detracts from the fact that their actions humanitarian reflected the feeling and appreciation of the way of how to carry the war; a in a way that did not seek to cause unnecessary harm.